(untitled) - Kellerman, Jonathan (New York, 2019)
"LAPD Lieutenant Milo Sturgis is a fine homicide detective, but when he needs to get into the mind of a killer, he leans on the expertise of his best friend, the brilliant psychologist Dr. Alex Delaware. While Sturgis has a knack for piecing together the details of a crime, Delaware can decipher the darkest intents driving the most vicious of perpetrators. And there's no better place for the doctor's analytical skills to shine than a rowdy hall full of young men and women intoxicated on life and lust . . . and suddenly faced with the specter of death. Summoned to a run-down former strip joint, Delaware and Sturgis find themselves crashing a wild Saints and Sinners-themed wedding reception. But they're not the only uninvited guests. A horrified bridesmaid has discovered the body of a young woman, dressed to impress in pricey haute couture and accessorized with a grisly red slash around her neck. What's missing is any means of identification, or a single partygoer who recognizes the victim. The baffled bride is convinced the stranger snuck in to sabotage her big day--and the groom is sure it's all a dreadful mistake. But Delaware and Sturgis have a hundred guests to question, and a sneaking suspicion that the motive for murder is personal. Now they must separate the sinners from the saints, the true from the false, and the secrets from those keeping them. The party's over--and the hunt for whoever killed it is on"--
Booklist
Publishers Weekly
Adult
Keywords: Delaware, Alex (Fictitious character); Fiction; Sturgis, Milo (Fictitious character); Fiction; Murder; Fiction; Investigation; Mystery fiction